Embryo Germination Development of Coffea arabica L.at Various Media Composition, Subcultures Stages and Embryo Size - Rina Arimarsetiowati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2017)
Most reliable and efficient protocol for  Coffea arabica  L. of Sigararutang variety plant regeneration was established using embryoid as an early explant from the induction of embryogenic callus phase. A completely randomized designs with 5 replications was designed to accomplish 20 protocols of embryo germina-tion methods with different steps of subculture, size of embryo and germination medium. The embryogenic calluses from the flush leave explant were induced embryoid on a half-strength MS  medium fortified with a half-strength combina-tion vitamin of 1.8 mg/L nicotinic acid, 10.1 mg/L thiamin HCl and 3.1 mg/L pyri-doxine, 50 mg/L myo inositol, 33 mg/L L.cistein, 1 mg/L Kinetin, 0.1 mg/L NAA, 20 gr/L sucrose, 2.4 gr/L gelrite and pH 5.5.The result showed that Protocol 17 was the most effective, with 59,2% of rooted cotyledons, 4.04 cm of length of roots, 1.68 cm of length of hypocotyl, 20.8% of opened cotyledons and 100% of cotyledonary embryo at the end of 8 weeks which used the B medium, large embryos and twice phase of subculture from liquid medium to solid medium. The Protocol 17 is stable protocol from low to high value. Protocol 8 is the steady protocol from high to low value. Protocols 17 and 8 are the highest and lowest ranking, respectively, for each parameter. Protocol 17 is the most suitable for the germination embryo somatic.